2015
DOI: 10.1007/s00114-015-1307-2
|View full text |Cite
|
Sign up to set email alerts
|

Diet and nutrient balance of red panda in Nepal

Abstract: We identified the winter plant species consumed by red panda in the Dhorpatan Hunting Reserve of eastern Nepal and compared this to the early-summer diet which was determined previously by Panthi et al. (2012). In addition, we estimated the proximate nutritional content of the leaves identified in red panda diet for both seasons, and we used nutritional geometry to explore macronutrient balance of leaves from the two different sampling periods. We identified six different plants in winter scats, which were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…It can also help to adjust the amount of diet provided. Because diet requirements for red pandas vary with seasonal change (Nijboer & Dierenfeld, ; Panthi et al, ), continuous recording of body weight transition can be crucial to determine whether the change in body weight is caused by seasonal change or any health problem. Diet adjustments should be made based on the monitoring of body weight to prevent obesity or body weight loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also help to adjust the amount of diet provided. Because diet requirements for red pandas vary with seasonal change (Nijboer & Dierenfeld, ; Panthi et al, ), continuous recording of body weight transition can be crucial to determine whether the change in body weight is caused by seasonal change or any health problem. Diet adjustments should be made based on the monitoring of body weight to prevent obesity or body weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…They have developed plantigrade locomotion and enlarged radial sesamoids on their forelimbs, which are utilizing when climbing and grasping bamboo stems (Fisher, ). Seasonal nutrient preferences, such as increased carbohydrate intake in winter for thermogenesis and increased protein and lipid intake in early summer to support reproduction and lactation, have also been indicated (Panthi, Coogan, Aryal, & Raubenheimer, ; Wei, Wang, Feng, Li, & Zhou, ).…”
Section: Introductionmentioning
confidence: 99%
“…Red pandas generally inhabit dense bamboo thicket under-stories [24,30,45,53]. Being bamboo specialists, more than 80% of their diet consists of bamboo grass [2932,54]. Previous studies in this region also have shown strong associations between red panda presence and habitats with understorey cover dominated by bamboo grass [26,53].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of red panda ecology in Nepal Himalayas, Northeast India, and Bhutan largely focused on assessing their habitat and diet preferences [2932]. One study by Kandel et al [21] generated a predictive map of the species’ geographic range limits.…”
Section: Introductionmentioning
confidence: 99%
“…We used microhistological fecal analysis (Holechek & Gross, ) to determine the diet composition (% relative frequency [RF%]) of black bear following Panthi et al (), Panthi et al (). Reference samples (plants and insects) were collected from the study areas for microhistology.…”
Section: Methodsmentioning
confidence: 99%